Atchison, Atchison County - Franklin, Brent (Kansas State University, The Chapman Center for Rural Studies, 2011)
This study contains information about the first settlement called Atchison, Atchison County, in the year 1855. It includes historical accounts, both told by historians and in primary sources, and shows the earliest illustrations of the town. The study will be centered on the life of the small riverfront town during its first years as a pro-slave community and on the events that changed it from the pro-slave outlook to the free-state town you see today.
Brent Franklin, “Atchison, Atchison County,” Chapman Center Research Collections, https://ccrsresearchcollections.omeka.net/items/show/38.
Keywords: Atchison; New England Immigrant Aid Society; Samuel Pomeroy; George Million; free-state; The Great Detour